Individual Performance on Self-Efficacy and Oranization Commitment Mediated by Job Satisfaction During the Covid-19 Pandemic - Astika, Ida Bagus Kompyang; Sawitri, Dyah; Cicikwijayanti, Tri (Enrichment: Journal of Multidisciplinary Research and Development, 2023)
This study aims to analyze the effect of: (1) individual performance on self efficacy, (2) individual performance on organizational commitment, (3) individual performance on job satisfaction, (4) job satisfaction on self efficacy (5) job satisfaction on organizational commitment, (6) individual performance on self efficacy through job satisfaction, (7) individual performance on organizational commitment through job satisfaction. This research was conducted at the Bali Regional Development Bank Singaraja Branch Office using an explanatory research approach with a saturated sample obtained by 40 employees. Data collected by questionnaire method is given directly to respondents, then analyzed using path analysis. However, previously tests of validity, reliability and classical assumption tests were carried out. His hypothesis was tested with the 1-test and to determine his mediating role the Sobel test was used. The results concluded that, all hypotheses proposed were accepted, namely: (1) individual performance has a positive effect on self efficacy, (2) individual performance has a positive effect on organizational commitment, (3) individual performance has a positive effect on job satisfaction, (4) job satisfaction has a positive effect on self efficacy, (5) job satisfaction has a positive effect on organizational commitment, (6) individual performance has a positive effect on self efficacy through job satisfaction, (7) Individual performance positively affects organizational commitment through job satisfaction.